Expeditious Quantification of Lignocellulolytic Enzymes from Indigenous Wood Rot and Litter Degrading Fungi from Tropical Dry Evergreen Forests of Tamil Nadu. (26th February 2014) - Sudarson, Jenefar; Ramalingam, Shenbhagaraman; Kishorekumar, Premalatha; Venkatesan, Kaviyarasan
Abstract : In this study thirty wood rotting and litter degrading basidiomycetes were screened for the production of lignocellulolytic enzymes such as, laccase, peroxidase, and cellulase using rapid micro quantification assay. Out of the 30 indigenous isolates Trametes gibbosa was identified to be a potential lignocellulolytic enzyme producer, producing a maximum amount of cellulase (299 .66 ± 1 .59  IU/L) and laccase (257 .94 ± 1 .79  U/L). Moreover, it is the second leading producer of peroxidase enzyme (170 .19 ± 1 .98  U/L). Tricholomopsis sp. a wood rot basidiomycete was found to be the leading lignin decomposer with maximum peroxidase activity (287 .84 ± 2  U/L) and second maximum laccase activity (250 .19 ± 1 .83  U/L). However, its cellulolytic potential was found to be moderate (100 .04 ± 1 .13  U/L). A higher level of lignocellulolytic enzymes was recorded in wood rotting basidiomycetes, whereas very low levels of lignolytic enzymes were found in litter inhabiting basidiomycetes. However, their cellulolytic potential was found to be moderate.